Potentials, challenges and future of chimeric antigen receptor T-cell therapy in non-Hodgkin lymphomas. (2nd July 2020) - El-Galaly, Tarec Christoffer; Cheah, Chan Yoon; Kristensen, Daniel; Hutchison, Andrew; Hay, Kevin; Callréus, Torbjörn; Villa, Diego
Abstract: Background: Diffuse large B-cell lymphoma (DLBCL) is the most common lymphoma subtype. Disease progression or relapse following frontline chemoimmunotherapy, largely in the form of standard R-CHOP, occurs in 30–40% patients. Relapsed/refractory (R/R) DLBCL represents a major unmet medical need. In particular, patients with primary refractory disease or those whose lymphoma relapses after autologous stem cell transplantation have historically had poor outcomes. Material and methods: Chimeric antigen receptor T-cell (CART) therapy is a promising novel treatment with curative potential in this setting. CART is based on ex vivo genetic modification of autologous T-cells to express chimeric receptors targeting antigens highly expressed in tumors such as CD19 in DLBCL. After lymphocyte-depleting therapy, patients are infused with CARTs that expand in vivo and target CD19-positive lymphoma cells. Results: In initial phase I–II trials, investigators have demonstrated complete responses in 40–50% of patients with R/R DLBCL, resulting in durable remission approaching 3 years of follow-up in most of these patients without further treatment. The logistics of delivery are complex as cell products require timely long-distance transfer between hospitals and production facilities. The unique toxicity profile of CARTs, including the risk of fatal immunological and neurologic events, also requires specific hospital wide management approaches and education. The substantial direct and indirect costs of CART will limit access even in countries with well resourced health care systems. Conclusions: While only two products are commercially available at present, further approvals in coming years appear likely. Future directions include CARTs with reactivity to tumor antigens other than CD19 and products targeting multiple tumor antigens to overcome resistance. The availability of CART has altered the current treatment algorithm for R/R DLBCL, and indications will likely expand to earlier lines of therapy and other hematologic malignancies.